Аналіз стану технічного забезпечення галузі рослинництва в Запорізькій області - Прус, Юрій Олександрович; Prus, Yurii; Прус, Юрий Александрович (My University, 2013)
UK: В роботі досліджено рівень технічного забезпечення галузі рослинництва в Запорізькій області, досліджено віковий стан тракторів і комбайнів, динаміку їх вибуття та надходження і розподіл за термінами випуску та місцем виробництва, склад та динаміку власних джерел відтворення основних фондів у сільськогосподарських підприємствах. Вказано на необхідність створення ефективної програми забезпечення аграрного сектора сучасними сільськогосподарськими машинами та механізмами і формування системи їх технічного обслуговування і ремонту. EN: Abstract – article purpose to carry out the analysis of a current state of technical maintenance of plant growing in various forms of agrarian enterprises of the Zaporizhya area and to define the basic directions of increase of its level. Insufficient receipt in the agricultural enterprises of new techniques constrains writeoff of outofdate techniques and promotes increase in degree of deterioration of available techniques. The techniques most part has fulfilled one standard term of use. Agricultural commodity producers use techniques mainly a domestic production. Acquisition of techniques of foreign manufacture intensively occurred recent years. The analysis shows that tractors are got mainly in the primary market, and combine harvesters on secondary. The basic sources of financing of acquisition of new techniques are means from amortisation, profit, and means of the state support. It is established that constant inflationary growth of operational expenditure distracts a considerable share of these sources on financing of circulating assets. For the purpose of timely and qualitative performance of a full complex of agricultural works with application it for technologies saving energy is necessary to develop state and regional programs of maintenance of agrarian sector by modern agricultural machines and mechanisms and to generate maintenance service and repair organizational structures of them. Important direction of improvement of technical and technological maintenance of agrarian manufacture is creation of a network of the regional versatile agrotechnological centres.
The analysis of the condition of technical maintenance of plant growing in the Zaporizhya area
Keywords: сільськогосподарська техніка; стан техніки; технічне забезпечення; сільськогосподарські підприємства; аgricultural machinery; techniques’ condition; loading on techniques; the agricultural enterprises